(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Writing this paper aims to describe the design of the User Interface and User Experience designs that can be used in the service delivery application of a company in Indonesia. This design useful for making the application display easier to understand, comfortable to view, and comfortable to use.The use of the user interface design will be applied to mobile applications that will be used by customers of delivery services. In the delivery service, there will be several forms of service that differentiate it from similar companies.